A gene for familial venous malformations maps to chromosome 9p in a second large kindred. Issue 3 (March 1995) - Gallione, C J; Pasyk, K A; Boon, L M; Lennon, F; Johnson, D W; Helmbold, E A; Markel, D S; Vikkula, M; Mulliken, J B; Warman, M L
Abstract : Venous malformations are a common form of vascular anomaly that cause pain and disfigurement and can be life threatening if they involve critical organs. They occur sporadically or in a familial form, where multiple lesions are usually present. We have identified a large kindred showing autosomal dominant inheritance of venous malformations. Using this family we confirm linkage of a familial form of venous malformations to chromosome 9p. We suggest that blue rubber bleb naevus syndrome can be considered a particular manifestation of this form of familial venous malformations. The candidate region for this gene encompasses the interferon gene cluster and the MTS1 (p16) tumour suppressor gene.